Castles & forts - Adams, Simon, 1955-; Rogers, Clifford J. (Boston : Kingfisher, 2007)
An illustrated exploration of a wide array of castles and fortifications throughout the world, from Norman mottes to Maori forts, including how and why they were built and their importance in history.
Includes bibliographical references and index.
8.3
5-8
Keywords: Fortification -- Juvenile literature; Castles -- Juvenile literature; Fortification; Castles; Fortification; Castles